When less confident forecasts signal more expertise - Palmeira, Mauricio; Heath, Timothy B. (Organizational behavior and human decision processes, 2025)
•We identify reflective thinking as an important moderator of the confidence heuristic.•Reflective thinkers view moderately confident advisors as more expert than highly confident ones.•The impact of reflective thinking disappears when there is high situational certainty.•Greater confidence variability also increases perceptions of expertise. The confidence heuristic indicates that people infer greater expertise from forecasters who express higher confidence. In the present research, we identify two key conditions under which this heuristic breaks down and even reverses. First, we find that cognitive reflection plays a moderating role: less reflective thinkers (as measured by the Cognitive Reflection Test; Frederick 2005) interpret high confidence as a sign of expertise, whereas more reflective thinkers tend to view it as a signal of incompetence—unless contextual cues suggest high situational certainty. We demonstrate this reversal in both evaluations of a single forecaster and choices between forecasters. Second, we show that when advisors make multiple predictions, variability in their expressed confidence serves as an additional cue to expertise. As a result, advisors can even appear more expert by lowering their average confidence while increasing the variability. We provide evidence for these effects across diverse domains, including financial advice, product performance, and sports outcomes.